The self-presentation of Pepyankh the Middle at Meir: scandal, religious institutions and participation, the next world - Baines, J (Museum Tusculanum Press, 2015)
The setting of the longer inscriptions of Pepyankh the Middle at the back of the outer court of his tomb at Meir is discussed. Annotated metrical transcriptions and translations are presented for the lintel text, captions to figures, and the biographical inscriptions, which together form a unity. The titles on the lintel give a sense of the protagonist’s official role. The main southern inscription, to be read first, deals with more public aspects of Pepyankh’s life, during which he had been accused of improper action. It also asks the audience to perform a ‘beatification of Hathor’, perhaps at a festival or in a mortuary chapel in the city. The northern inscription is primarily about religious matters. Pepyankh claims merit for his performance of the cult of the ungendered deity Hathor and for other ethical actions. The text mobilizes the conception that a good life will benefit the deceased in the hereafter, and this would fit with a belief in judgment after death.